Modeling and control of modern electrical energy systems - Karimi-Ghartemani, Masoud (IEEE Press series on power and energy systems, 2022)
In Modeling and Control of Modern Electrical Energy Systems, distinguished researcher Dr. Masoud Karimi-Ghartemani delivers a comprehensive discussion of distributed and renewable energy resource integration from a control system perspective. The book explores various practical aspects of these systems, including the power extraction control of renewable resources and size selection of short-term storage components. The interactions of distributed energy resources (DERs) with the rest of the electric power system are presented, as is a discussion of the ability of the DER to ride through grid voltage faults and frequency swings. Readers will also discover how to derive mathematical models of different types of energy systems and build simulation models for those systems.